PERANCANGAN SISTEM REMOTE IP TABLE DAN INSTRUSION DETECTION SYSTEM (IDS) DENGAN SNORT PADA JARINGAN LAN - Adhi Prakosa, Bayu; Hendrawan, A. Hendri; Apriana, Windi (Krea-TIF: Jurnal Teknik Informatika, 2015)
The design of Remote Iptables and Intrusion Detection System (IDS) system with Snort has been done. Local Area Network Model Network is widely applied to various customer segments. Problems of decreasing LAN network performance, due to a number of ping of death attacks and SYN flooding attacks that affect all computers connected on the LAN network. Based on that, we need a proper attack detection and prevention system to help the administrator in LAN network security. Remote Iptables and Intrusion Detection System with Snort, warning system of real-time attacks will be sent via SMS, a number of syntax with iptables remote using SMS Gateway, and blocking in real time. Stages used for the achievement of research objectives, is the identification of problems, design system requirements, system implementation and testing. Detection results are 4 (four) types of information, ie attack time, type of destination IP attack, and IP source. Detection and blocking of attacks based on a number of syntax is done by comparing the packet to the rules in the form of integration through SMS Gateway for the ease of the administrator in the execution of blocking. Blocking attacks in the form of 3 (three) types of information, the source IP, the type of attack, and security policy. Based on these results, some attacks can be detected in real time against 4 types of information, blocking attacks integrated via SMS Gateway in the form of packet comparisons to rules, and blocking attacks in the form of Remote Iptables with 3 (three) types of information. Keywords: LAN Network, Remote Iptables, Intrusion Detecion System, SMS Gateway.